Racial differences in stage IV colorectal cancer survival in younger and older patients - Wallace, Kristin (Clin Colorectal Cancer, 2016)
INTRODUCTION: African Americans (AA) compared to European Americans (EA) have poorer stage specific survival from colorectal cancer (CRC). Recent reports have indicated that the racial difference in survival has worsened over time, especially among younger patients. To better characterize this association, we used population-based SEER registry data to evaluate the impact of race on stage IV CRC survival in patients < 50 and ≥ 50. PATIENTS AND METHODS: The population was comprised of 16,782 patients diagnosed with stage IV colon and rectal adenocarcinoma between 01 January 2004 and 31 December 2011. Cox proportional hazards regression was used to evaluate the association between race and other prognostic factors and the risk of death in each age group. RESULTS: Younger AAs compared to EAs had a higher prevalence of proximal CRC at diagnosis, a factor associated with significantly higher risk of death in both races. Among patients < 50 years of age, AAs had a higher risk of death compared to EAs (HR 1.35, 95% CI 1.20 to 1.51)), which was attenuated in patients ≥ 50 years of age (HR 1.10, 95% CI 1.04 to 1.16); p for interaction 0.01. CONCLUSION: The results revealed poor overall survival in AA compared to EA, especially in those < 50 years of age. The higher prevalence of proximal CRC at diagnosis among younger aged AA (vs. EA) may contribute to the racial difference in survival. Future studies will be needed to understand how colonic location impacts the efficacy of treatment regimens.